(untitled) (The Research of Medical Science Review, 2025)
Chronic low back ache (CLBA) is the prevalent condition that significantly impacts the quality of life. This study aims to explore the causes of chronic low back ache and its associated MRI findings in the patients. The cross-sectional observational study of 100 patients is conducted, reviewing the MRI scans for structural abnormalities. The most common findings were disc degeneration (15%), spinal stenosis (63%), and facet joint osteoarthritis (6%), Modic changes. A correlation between disc degeneration severity and reported pain intensity was observed. These results underline the importance of MRI in diagnosing CLBA and suggest that MRI-guided treatment strategies may enhance patient care.